(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Dilated Cardiomyopathy (DCM) is a form of cardiomyopathy characterized by left ventricular or biventricular dilatation and impaired ventricular contractility. This results in systolic dysfunction of the heart with decreased left ventricular ejection fraction and progressive cardiac failure. This case report describes the successful anaesthetic management of a parturient with Dilated cardiomyopathy underwent Caesarian section under spinal anaesthesia. Chatt Maa Shi Hosp Med Coll J; Vol.18 (1); Jan 2019; Page 52-53